Rediscovery of the red-listed grass Isachne dimyloides (Poaceae: Micrairoideae) 130 years after type collection - Devi, Moonmee; Bhattacharyya, Debjyoti (Phytotaxa, 2015)
This paper reports rediscovery of a rare grass Isachne dimyloides after a gap of 130 years since its type collection. The type locality of the species is the Darjeeling district of West Bengal, India and the collection was made by C.B. Clarke in the year 1884. The present collection was made in 2012 from Cachar district of Assam (India) which also indicates its geographic range extension from the Darjeeling foothills to the Assam floodplain. In this paper a description of the species, a key, and an illustration are provided to facilitate identification. Priority conservation is highly recommended for this rare species.